3. Effects of Administration of Combination of Palm Kernel Meal, Katuk Leaf and Betel Nut Powder on Sensory Value of Meat In The Goat - Teuku Reza Ferasyi; Hamdani Hamdani; Razali Razali; Yudha Fahrimal; Teuku Shaddiq Rosa (The Faculty of Veterinary Medicine of Syiah Kuala University, 2016)
In goats, we tested the sensory value of meat in the goat after oral treatment with palm kernel meal (PK), katuk leaf powder (KL) and betel nut powder (BN), separately and in combination. This study were used 8 Boerka goats that allocated among four groups of 2: the Control group was given distilled water; PK only was given to Group P1; a combination of all three was administered to Group PK-KL-BN, and a combination of KL and BN was administered to Group KL-BN. All treatments were administered orally for 35 consecutive days. animals were weighed before treatment (Day 0) and on Day 40 (5 days after the end of treatment). On day of 40, the animals were slaughtered using halal standard. Then, sample of meat was taken from bicep femoris of right leg of each animals for sensory evaluation, which comprised of tenderness, colour, aroma, taste, and juiciness. A number of 30 panelist were involved in the evaluation. The results showed that the meat were tender in the group of PK-KL-BN and KL-BN (the hedonic scale of 2, tender). Then, for the other parameters were not different between groups. In conclusion, the administration of combination of palm kernel meal, katuk leaf powder and betel nut powder, can improve the tendernes of meat in goats.